Channel Coding Analysis for High-Speed Telecommunication System - Saw, Khin; Yin Win, Lei Lei; Myo Tun, Hla; Win, Thanda; Aye, Mya Mya; Kyu Kyu Win, Khin; Pradhan, Devasis (Journal of Novel Engineering Science and Technology, 2025)
The paper mainly focuses on the channel coding design for high-speed telecommunication systems. The challenging issues in this study are based on (1) the growing demand for high data speed and an increase in subscribers, and (2) high-speed telecommunication networks allow users to avoid them due to better speed and more bandwidth. The objectives of this study are (1) to obtain a higher data rate, higher spectral efficiency, higher throughput, higher bandwidth, and higher energy efficiency at lower latency and (2) to detect/correct errors caused when information is transmitted through noisy channels. Therefore, high-speed telecommunication channel coding techniques will play a major role in achieving fast communication with minimum errors. The linear block and turbo codes are fundamental to analyzing the channel coding scheme for specific purposes. Theoretical concepts with numerical simulation are used to conduct the analyses. The simulation results on BER analyses confirm that the performance criteria could be met with real-world applications.